Fenugreek (Trigonella foenum-graecum) extract improves hyperglycemia and hyperlipidemia in high sugar diet fed mice - Chacrabati, R; Afrin, T; Hasan, MK; Goswami, C (Bangladesh Journal of Animal Science, 2022)
Diabetes, obesity and other cardiovascular diseases are major public health problems that are increasing at an alarming rate. Diabetics and obesity are characterized by high blood glucose level caused by high sugar consumption. New treatment techniques are needed that can lower blood glucose levels without causing any negative effects. Fenugreek known as Methi in Bangla, has been well known to have medicinal properties, such as antidiabetic, anti-hyperlipidaemic, anti-inflammatory, anticancer, antioxidant, and neuroprotective activities. Thus, the supplementation of fenugreek could be an alternative diet that could mitigate the deleterious effect of high sugar consumption and prevent the development of metabolic diseases. Therefore, this experiment was designed to investigate the effect of Fenugreek extract (FE) supplementation on anti-hyperglycemic and anti-hyperlipidemic activities in high sugar diet (HSD) fed mice. Four diet paradigms were selected for this experiment- viz., normal diet (ND), normal diet with Fenugreek extract (ND+FE), 30% sucrose (HSD), and 30% sucrose with Fenugreek extract (HSD+FE). The supplementation of FE (300mg/kg BW) significantly (*p<0.05) hampers the increase in food intake due to high sugar diet consumption in mice. Additionally, mice fed with FE enriched diet significantly lowered body weight as compared with the HSD group. Also, FE supplementation significantly attenuated the increased blood glucose concentration caused by high sugar intake. The inclusion of FE had no effect on heart weight, kidney weight, white adipose tissue and brown adipose tissue but significantly decreased the increased weight of the liver in the HSD-fed group. In addition, FE supplementation also attenuated the HSD-induced elevation of serum total cholesterol (TC), triglycerides (TAG), and low-density lipoprotein C (LDL-C). Considering the above findings, FE could effectively tolerate a normoglycemic state and inhibit the development of diabetics and obesity caused by HSD. Therefore, FE could be beneficial for the management of metabolic disorders due to consumption of high sugar. Bangladesh Journal of Animal Science 51 (3): 90-97, 2022